PENERAPAN MODEL PEMBELAJARAN INQUIRY TERHADAP KEMAMPUAN MENENDANG BOLA PADA PERMAINAN SEPAK BOLA SISWA SDN 19 WOJA DOMPU - Muhaimin, Muhaimin; Soemardiawan, Soemardiawan; Rindawan, Rindawan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
From the results of observations made in class V SDN 19 Woja Dompu District, it was found that the classical completeness obtained was far from the determined indicators. The low student learning outcomes are thought to occur because the presentations are more often used methods that do not practice soccer playing techniques. The Inquiry learning model invites students to be able to practice their ability to improve problem solving skills so as to improve learning outcomes and technical ability to kick the inside foot and instep in soccer games. Research Objectives To find out the application of Inquiry learning model can improve the basic technical skills of kicking a ball in a soccer game for students of SDN 19 Woja Dompu Regency in the 2018/2019 school year? The design of this study was classroom action research conducted in 2 cycles consisting of the planning stage, with a sample of 24 students in class V of SD Woja implementation, observation, evaluation and reflection. Research data in the form of student learning outcomes were taken by assessment techniques in the form of student observation sheets according to indicators of achievement of soccer game material. Based on data analysis formative assessment results show that in the first cycle of students who completed their learning outcomes as many as 15 people or 62.5% and those who have not yet completed learning as many as 9 people or 37.8%. While in cycle II students who completed their learning outcomes were 21 people or 87.5 %% and those who did not complete as many as 3 people or 8.70%. So the mastery learning of fifth grade students at Woja Elementary School in cycle II has reached the level of mastery learning set by the school which is at least 75%. The conclusion of this research is the application of the Inquiry model to improve the ability of the basic technique of kicking the inside foot and instep on a soccer game for students of SDN 19 Woja Dompu Regency in 2018/2019 Academic Year.